Detecção da linfocitose B monoclonal com fenótipo de leucemia linfocítica crônica e avaliação das subpopulações linfocitárias em indivíduos de origem nipônica residentes no Brasil - Moss, Mariane de Faria [UNIFESP] (2017)
Introduction: Chronic Lymphocytic Leukemia (CLL) is the most common leukemia in the Western world, with an incidence of more than 3 cases per 100,000 individuals per year. However it is rare in Japanese, with an estimated incidence of 0.2 to 0.3 per 100,000 people per year. It is known that prior to the disease’s onset, CLL is preceded by an asymptomatic form, Monoclonal B lymphocytosis (MBL), where small amounts of cells with CLL phenotype are found in peripheral blood of healthy individuals. The MBL is separated into two distinct, low-count (<0,5x109 clonal B cells/L) and high-count groups (≥0,5×109 and <5,0x109 clonal B cells/L), the second group is usually accompanied by lymphocytosis and has been shown to be more likely to progress to CLL. Objectives: To evaluate the MBL in individuals of Japanese origin living in São Paulo. To evaluate the counts of the lymphocyte subpopulations in this population and to relate the presence of MBL with the B lymphocyte subpopulations. Methods: It was studied 268 volunteers without racial miscegenation, with age greater than or equal to 40 years (median 66, ranging from 40 to 96 years), being 42% of the male gender. Peripheral blood samples were used to perform the blood count and immunophenotyping by 8-color flow cytometry. The MBL was classified according to the phenotype: CLL-like MBL (CD19+, CD20low and CD5+), atypical CLL-like (CD19+, CD20high, CD5+ and variable CD23 expression) and non-CLL-like (CD19+CD5-). Purified MBL cells were obtained by sorting for molecular study of IgVH gene mutation and by FISH to study chromosomal abnormalities. The B lymphocyte subpopulations were identified according to the following phenotypes: immature B (CD19+, CD20+, CD38++, CD27-, CD10+, sIgM++, CD45+); Naive (CD19+, CD20+, CD38-/+, CD27-, sIgM+, CD10-, CD45+); B memory (CD19+, CD20+, CD38-/+, CD27+, sIgM-/+, CD10-, CD45+) and plasmocytes (CD19+, CD20-/low, CD38+++, CD27++, CD10-, sIgM-/+, CD45+). Results: The MBL was detected in 10% of cases. All clones had CLL phenotype. The median value of the MBL clone was 0.08% (0.01-19.8%) of B lymphocytes and 116x10³/L (31-19,800x10³/L). The frequency of MBL showed progressive increase with age, varying from 3.8% in individuals aged 40-59 years to 21.4% in those aged over 80 years (p=0.04). In a comparative analysis between individuals with and without MBL, there was no difference in B lymphocyte counts, there were differences only between T lymphocytes (p=0.049) and NK cells (p=0.002), both higher in cases with clone presence. The study of IgVH gene mutation was performed in five cases. All mutated cases were VH3: IgVH3-7.01, IgVH3-48 (2 cases) and IgVH3-21. The only non-mutated case was IgVH1-8. It was possible to perform FISH in seven cases and no chromosome abnormality was found. The total B lymphocyte values showed a reduction with progressive increase of age (p<0.001). The same occurred in relation to the subpopulations B Memory (p=0.001), Naive (p=0.001), immature B (p=0.047) and plasmocytes (p=0.011). In men, there was a decrease as the age increases in leukocyte counts (p=0.049), T lymphocytes (p=0.005), TCD4 (p=0.005), TCD8 (p=0.025) and NK cells (p=0.001), while there was a tendency to a lower value in total lymphocytes (p=0.070). However, in women there was only a decrease in total lymphocyte counts (p=0.020) and a trend towards a lower TCD8 lymphocyte count (p=0.080). Conclusions: The frequency of MBL in the Japanese population was similar to that reported in Western individuals. Most clones had CLL phenotype and all were low counts. Lower B and T lymphocyte counts were found in men and in the older age group.